2004
DOI: 10.1136/bmj.329.7466.584
|View full text |Cite
|
Sign up to set email alerts
|

Doctors and nurses with HIV and AIDS in sub-Saharan Africa

Abstract: “We're going to run out of people before we run out of money”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…Over the coming years, sub-Saharan African health systems may lose up to one-fifth of their employees to HIV/AIDS [3]. This attrition may have a severe impact on regional human resources for health capacity, leaving critical efforts, such as the general roll out of antiretroviral therapy (ART), barely feasible [7,8]. However, while health workers tend to know where to go to obtain an HIV test, reluctance to test and low access to post-exposure prophylaxis (PEP) has been found in the literature [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Over the coming years, sub-Saharan African health systems may lose up to one-fifth of their employees to HIV/AIDS [3]. This attrition may have a severe impact on regional human resources for health capacity, leaving critical efforts, such as the general roll out of antiretroviral therapy (ART), barely feasible [7,8]. However, while health workers tend to know where to go to obtain an HIV test, reluctance to test and low access to post-exposure prophylaxis (PEP) has been found in the literature [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…While the HIV prevalence rate among health workers in Malawi is not known, studies conducted elsewhere suggest that AIDS is a major cause of death among health workers in high prevalence countries (World Health Organization [WHO], 2006). In South Africa a study conducted by Human Sciences Research Council (HSRC) found a prevalence rate of 15.7% amongst health workers and that between 1997 and 2001, 13% of the health workers had died from HIV- and AIDS-related illnesses including TB (Ncayiyana, 2004; Shisana et al, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…In many African countries, current concerns about the health labour market focus on overall poor working conditions, shortages of skilled personnel, skewed distributions within countries, a rapidly increasing external brain drain and impact of HIV/ AIDS, which is aggravating and accelerating these problems (Dovlo 2005;Kober & Van Damme 2004;Narasimhan 2004;Ncayiyana 2004;Thupayagale-Tshweneagae 2007;Van Damme et al 2008;WHO & UNAIDS 2006). Adaptation of actual ART delivery models (which are doctor-intensive) to make them less HRH-intensive is needed (Dovlo 2004;Hongoro & McPake 2004).…”
Section: Introductionmentioning
confidence: 99%